Interpopulation Variations in Behavioral Syndromes of a Jumping Spider from Insecticide‐Treated and Insecticide‐Free Orchards. (8th November 2013) - Royauté, Raphaël; Buddle, Christopher M.; Vincent, Charles; Foster, S.
Abstract Variations in environmental conditions can influence behavioral syndromes (correlated tendencies in behaviors), and understanding the factors that shape trait covariation is particularly relevant when species are challenged by environmental changes. We investigated how behavioral syndromes varied at extremes of a gradient of anthropogenic disturbance, using apple orchards with different histories of insecticidal applications as a model system. Eris militaris (Araneae: Salticidae) jumping spiders were sampled from an insecticide‐free orchard and an insecticide‐treated orchard from Southern Québec. Spiders were tested for activity, aggression, boldness, and voracity under standardized conditions. Behavioral syndrome structure was compared between the two populations using Bayesian multiresponse models and structural equation modeling. Syndrome structure differed significantly between the two populations. The insecticide‐free population showed evidence of a syndrome involving all measured traits, while only aggression, boldness and voracity were correlated in the insecticide‐treated population. The insecticide‐free population showed negative correlations between active and voracious behavioral types vs. aggressive and bold types while the insecticide‐treated population showed a negative correlation between aggression‐boldness and voracity. This research is a first step in investigating the impact of anthropogenic disturbances on behavioral syndromes and demonstrates that behavioral syndromes may vary with respect to insecticidal applications.